Stability analysis and control of an active suspension system / [microfilm] - Kung, Kiew Li; Fakulti Kejuruteraan Mekanikal (2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2006